Tinjau Kondisi Fisik Wasit Sepak Bola PSSI Sumatera Selatan - Azizil Fikri; Popalri Popalri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to review the physical condition of the football referee PSSI South Sumatra. This type of research is descriptive. The sample uses total sampling technique. then the sample is 36 people. Data types are primary and secondary data. The data collection technique in this study was a running speed test of 6 x 40 meters with an average time of 6.2 seconds, followed by recovery time of 90 seconds back to the star and also a durability test running 20 x 150 meters with an average time of 30 seconds , followed by recovery for 50 seconds to walk 50 meters to the second star and so on. Based on data analysis, referee CIII resilience is in a sufficient category with an average of 13, meaning that referee CIII is only able to do 7 repetitions in running a field track. Referee CII is in the less category with an average of 10, this means that the CII referee is only able to do 5 repetitions in a single track run. Furthermore, the CI referee is in the best category with an average of 15, meaning that the CI referee is only able to do 5 repetitions in a single track run. The ability of the soccer referee PSSI South Sumatra's physical condition based on endurance tests is at a good level. Wit CIII seen in terms of speed is in the category very well with an average of 5, then the referee CII is in good category, and the referee CI is in excellent category . Conclusion, the physical condition of the football referee PSSI South Sumatra is in a very good category. Keywords: Physical Condition, Referee, Football